The impact of macroeconomic factors on Malaysia property performance during financial crisis / Nurhidayah Nordin (Faculty of Business and Management, 2007)
This project paper was designed to examine the impact of macroeconomic factors on a Malaysia real estate return series during financial crisis. The Asian financial crisis of 1997-2001 gives huge impact to Malaysian economy which shows the currency and stock market collapse. Besides that, other purpose of this study is to determine the relationship between interest rate, inflation, gross domestic product and unemployment rate with real estate's stock return. The relationship between property returns and the macro economy is important to investors1 strategies. Then, from this finding it shows whether there is weak or strong relationship between each variable. As for methodology, the analysis of this study covers a period of five years from 1997 to 2001 on quarterly basis. The data comprises of the independent variables that are interest rate, inflation, gross domestic product and unemployment rate while dependent variable is stock return on 30 property companies randomly selected in Main Board at Bursa Malaysia. All the data will be collected through secondary sources such as annual reports, Department of Statistics, Bank Negara Malaysia, and DataStream. For the data analysis, this research hypothesized the relationship between the real estate return and macroeconomic factors like interest rate, inflation, gross domestic product and unemployment rate and also the significant of each variable. The tools used for the analysis are Multiple Regression whiles the Statistical Package for Social Science (SPSS) as the statistical software. Pattern analysis based on correlation models reveals the ongoing macroeconomic links with major property markets.